2023
DOI: 10.1001/jamanetworkopen.2023.18611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine on Posttraumatic Stress Disorder in Patients Undergoing Emergency Trauma Surgery

Abstract: ImportancePosttraumatic stress disorder (PTSD) is common in people who have experienced trauma, especially those hospitalized for surgery. Dexmedetomidine may reduce or reverse the early consolidation and formation of conditioned fear memory and prevent the occurrence of postoperative PTSD.ObjectiveTo evaluate the effects of intraoperative and postoperative low-dose intravenous pumping dexmedetomidine on PTSD among patients with trauma undergoing emergency surgery.Design, Setting, and ParticipantsThis double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In our study, we did not find any effect of dexmedetomidine on quality of life and cognitive failure 3 months after surgery. It also has been reported that dexmedetomidine could exert a protective effect against fear memory and anxiety behaviour, potentially preventing PTSD [ 31 33 ]. In our study, the proportion of PTSD, as an exploratory outcome, was less important in the patients receiving dexmedetomidine compared to placebo (1.9% vs. 5.2%), but the result was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not find any effect of dexmedetomidine on quality of life and cognitive failure 3 months after surgery. It also has been reported that dexmedetomidine could exert a protective effect against fear memory and anxiety behaviour, potentially preventing PTSD [ 31 33 ]. In our study, the proportion of PTSD, as an exploratory outcome, was less important in the patients receiving dexmedetomidine compared to placebo (1.9% vs. 5.2%), but the result was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive Care Unit (ICU)-acquired delirium is a severe complication of critical illness characterized by acute brain dysfunction, including inattention, disturbance of consciousness, and changes in cognitive function ( 8 ). To detect and prevent delirium in a timely manner, the Richmond Agitation-Sedation Scale (RASS) and Cornell Assessment of Pediatric Delirium (CAPD) were administered to the patient every 12 hours ( 9 - 11 ). Several studies have indicated that delirium can be caused by various medications, although the exact reasons remain unclear ( 9 - 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…To detect and prevent delirium in a timely manner, the Richmond Agitation-Sedation Scale (RASS) and Cornell Assessment of Pediatric Delirium (CAPD) were administered to the patient every 12 hours ( 9 - 11 ). Several studies have indicated that delirium can be caused by various medications, although the exact reasons remain unclear ( 9 - 11 ). Delirium can lead to adverse effects such as increased mortality, prolonged hospital stay, and negative impacts on growth and development ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%